Peningkatan Pemahaman Investasi Terhadap Masyarakat Dukuh Pakis - Panjaitan, Gary Gilbert Goklas; Ira Wikartika (Politeknik Kampar, 2023)
Abstract: Investment is one of the important ways to optimize finances and achieve long-term financial goals. However, there are still many people who lack adequate knowledge and understanding of investment. In this abstract, we discuss the importance of investment education in increasing public awareness and knowledge about investment. Many people still consider investment as complicated, risky, or only limited to certain circles. Therefore, investment education is very important in opening people's insights about the benefits of investment and providing an understanding that investment can be accessed by anyone. Many people don't understand the difference between stocks, bonds, mutual funds, property, and other investment instruments. Investment education can help provide basic knowledge about different investment instruments, as well as help individuals understand the risks and potential benefits associated with each instrument